2016
DOI: 10.1016/j.tet.2016.05.028
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of (2 R ,8′ S ,3′ E )-δ-tocodienol, a tocoflexol family member designed to have a superior pharmacokinetic profile compared to δ-tocotrienol

Abstract: A group of side chain partially saturated tocotrienol analogues, namely tocoflexols, have been previously designed in an effort to improve the pharmacokinetic properties of tocotrienols. (2R,8′S,3′E,11′E)-δ-Tocodienol (1) was predicted to be a high value tocoflexol for further pharmacological evaluation. We now report here an efficient 8-step synthetic route to compound 1 utilizing naturally-occurring δ-tocotrienol as a starting material (24% total yield). The key step in the synthesis is oxidative olefin clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The fate of the tocol depends on the preferential binding of ATTP in the liver, and those that are not selected by ATTP are excreted via bile or renal excretion ( Figure 2 ) [ 25 , 61 ]. ATTP has a much greater affinity AT than for all other tocols, and this would explain why the other tocols exhibit lower plasma levels over time [ 62 , 63 , 64 ]. Vitamin E supplements are commonly formulated with AT, which is often present as a synthetic racemic mixture.…”
Section: Vitamin E Tocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of the tocol depends on the preferential binding of ATTP in the liver, and those that are not selected by ATTP are excreted via bile or renal excretion ( Figure 2 ) [ 25 , 61 ]. ATTP has a much greater affinity AT than for all other tocols, and this would explain why the other tocols exhibit lower plasma levels over time [ 62 , 63 , 64 ]. Vitamin E supplements are commonly formulated with AT, which is often present as a synthetic racemic mixture.…”
Section: Vitamin E Tocolsmentioning
confidence: 99%
“…This can be achieved by increasing the affinity of the analogs to ATTP, which may be responsible for maintaining the plasma levels of these compounds and also by increasing their permeability. Multiple studies [ 25 , 63 , 66 ] have recently reported the development of such analogs, the tocoflexols ( Figure 3 ). The tocoflexols were designed, using computer aided techniques, to behave like tocopherols in terms of their bioavailability and like tocotrienols in terms of their biological activity.…”
Section: Vitamin E Tocolsmentioning
confidence: 99%
“…We have previously reported the synthesis of chloride 2 via aldehyde 4 using δ-tocotrienol as a starting material. [14] Synthesis of sulfone 3 started from commercially available 5-hydroxypentan-2-one (6). Protection of the hydroxy group of 6 with tert-butyldimethylsilyl (TBS) gave compound 8, which was converted to ester 9 as a mixture of Z/E isomers [15] in a ratio of~1 : 2 (determined by GC-MS analysis).…”
Section: Synthesis Of Dt3-f2mentioning
confidence: 99%
“…Compounds 20 and 21 were prepared in a similar way to the synthesis of 2. [14] Briefly, the OH group of δ-tocotrienol was initially protected with a methoxymethyl (MOM) group to afford 23, which was followed by double bond cleavage to form aldehyde 24 and transformation into α,β-unsaturated esters with E-isomer 25 as the major product (Z/E ratio of~1 : 9, according to GC-MS). Reduction of 25 with DIBALÀ H gave alcohol 26, which was converted into chloride 20 and bromide 21 by standard methods (Scheme 3).…”
Section: Synthesis Of Dt3-f2mentioning
confidence: 99%
See 1 more Smart Citation